Evaluation of breast cytology by applying modified Masood’s scoring system - Jyoti Yadav,; Pushpa Batham,; Sharma DB, (Asian Journal of Medical Sciences, 2023)
Background: The occurrence of breast cancer is increasing worldwide with peak incidence occurring above the age of 50 years in developed countries, whereas in india, it is above the age of 40. Fine-needle aspiration cytology (FNAC) is a quick, easy, and cost-effective diagnostic tool for breast disease, and also helpful to differentiate between various benign and malignant lesions of breast. Aims and Objectives: (1) to assess the usefulness of Modified Masood’s Scoring Index (MMSI) in breast cytology. (2) To study cytohistopathological correlation in breast lesions. After the FNAC of breast lesion, classify the breast lesion based on MMSI and histopathology. Materials and Methods: A hospital-based prospective study was conducted between March 2021 and September 2022 on 183 patients who were referred for FNAC from the surgery department to the cytology section of the Pathology Department at Netaji Subhash Chandra Bose Medical College Hospital in Jabalpur, Madhya Pradesh. Results: In our study, the largest group of cases (45.90%) was in the 20–39 age range, with a mean age of 37±14.65. The majority of cases (60.6%) belonged to category II (proliferative breast disease [PBD] without atypia) with a mean MMSI score of 11.35±5.55. The cytological findings showed a correlation of 98.20% with MMSI in category II and 88.68% in category IV, while the histopathological findings showed a correlation of 89.52% with MMSI category II and 98.15% with MMSI category IV. Fibroadenoma (FA) was the most common finding on histopathological examination, accounting for 120 cases (65.6%). Conclusion: The MMSI is an effective tool to complement cytomorphological diagnosis in breast lesions, including PBD with or without atypia and carcinomas. It is particularly valuable in the early management and prognosis of patients, as treatment options can vary based on the MMSI score.